Lower risk of fractures under methylphenidate treatment for ADHD: A dose–response effect. Issue 12 (7th September 2018) - Schermann, Haggai; Gurel, Ron; Ankory, Ran; Kadar, Assaf; Yoffe, Victoria; Snir, Nimrod; Sternheim, Amir; Karakis, Isabella
ABSTRACT: Methylphenidate (MP), a widely used and abused stimulant medication for ADHD, negatively affects bone mass. However, previous epidemiological studies demonstrated that MP is not associated with increased incidence of fractures in children, and may even have a protective effect due to behavior modification. This study aimed to investigate the association between MP and fracture risk in a retrospective cohort of healthy military recruits, aged 18–25, with at least 1 year of service between 2008 and 2017. Subjects were divided into five groups: subjects without ADHD; untreated subjects with ADHD; and subjects with ADHD and prescriptions of 1–90, 91–180, or 181+ tablets during the study period. The primary outcome was at least one fracture diagnosis during the study. Among 682, 110 subjects (409, 175 men [60%]), 50, 999 (7.5%) had fractures. MP was used by 1, 681 (0.4%) men and 2.828 (1%) women. The fracture rates in the no ADHD, untreated ADHD, ADHD 0–90, ADHD 91–180, and ADHD 181+ groups were 10.4%, 16.4%, 8.7%, 4.8% and 5.8% in men, and 3.6%, 7.1%, 4.6%, 4.4% and 3% in women, respectively. Multivariate regression analysis confirmed an inverse dose–response association between MP and fractures in men ( p  < 0.001). In women, untreated ADHD was associated with a significantly higher fracture risk, compared to healthy controls (OR = 1.82, p  < 0.001). The study confirms previous literature and demonstrates an inverse dose–response association between MP and fracture risk in men. © 2018 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 36:3328–3333, 2018. Abstract : Fracture incidence was compared between five groups of soldiers aged 18–25 with follow‐up of 12–82 months: subjects without ADHD; untreated subjects with ADHD; and subjects with ADHD and prescriptions of 1–90, 91–180, or 181+ tablets of methylphenidate during the study period. There was an inverse association between methylphenidate use and fracture incidence in men ( p  < 0.0001). In women, untreated ADHD was associated with a significantly higher fracture risk, compared to healthy controls (OR = 1.82, p  < 0.001).